2008
DOI: 10.1007/s10570-008-9239-z
|View full text |Cite
|
Sign up to set email alerts
|

CI Reactive Black 5 dye as a visible crosslinker to improve physical properties of lyocell fabrics

Abstract: Bi-functional reactive dyes have been used for reducing the fibrillation of lyocell fibres. The sole influence of CI Reactive Black 5 dye on the fibrillation tendency of lyocell single jersey knitted fabrics was investigated by dyeing with different concentrations (35 g/L for medium shade and 70 g/L for dark shade), dyeing without dyestuff and by decolouration process after each dyeing. The fibrillation tendency of lyocell fibres was accessed by means of fibre wet abrasion resistance and fibrillation number. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…Similar behavior has already been observed in cellulose fiber chemistry where modification of fiber fibrillation was attributed to the crosslinking of cellulose chains by RB5 …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Similar behavior has already been observed in cellulose fiber chemistry where modification of fiber fibrillation was attributed to the crosslinking of cellulose chains by RB5 …”
Section: Resultssupporting
confidence: 80%
“…Similar behavior has already been observed in cellulose fiber chemistry where modification of fiber fibrillation was attributed to the crosslinking of cellulose chains by RB5. 28 In the case of RB19, only one covalent bond is formed between the dye and a protein chain, thus dissolution of fibroin in CWE is not prevented by the formation of an interlinked molecular network. The presence of dyestuff molecules, which bear charged groups e.g., sulfonate groups will modify the solubility behavior of protein chains, however due to absence of crosslinks, the dissolution in CWE is not prohibited.…”
Section: Resultsmentioning
confidence: 99%
“…9(d), the Martindale pilling grade of EH-Lyocell was higher than Lyocell under all friction times except 3000 frictions. This was attributed to the cross-linking reaction between crosslinker EH and the hydroxyl group on cellulose, forming a three-dimensional network structure, which enhanced the transverse force of lyocell bers and the wear resistance of the fabrics (Bui et al 2009). With the increase of the number of frictions, the pilling grade of the lyocell fabrics gradually decreased until 1000 times, and then the grade rose.…”
Section: Characterizationsmentioning
confidence: 99%
“…Crosslinking is an effective treatment method to reduce the tendency of brillation by esteri cation or etheri cation reactions between ber macromolecular chains. Many researchers found that some ployfunctional reactive dyes can reduce the brillation of lyocell fabrics (Bates et al 2008;Bui et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has two azo chromophores and two vinylsulfone reactive groups in its molecular structure [1]. The scientific literature includes RB5 dye studies for different purposes [2][3][4][5]. Kyzas et al [6] investigated the adsorption of RB5 on magnetic graphene oxide.…”
Section: Introductionmentioning
confidence: 99%